The relationship between callosal axons and cortical neurons in the planum temporale: alterations in schizophrenia. - Simper, R; Walker, M; Black, G; Di Rosa, E; Crow, T; Chance, SA (2011)
The relationship between "connectivity" measures such as DTI and the cellular alterations in the cortex that give rise to those connections remains unclear. Cytoarchitectural changes in the planum temporale (PT) suggest impaired layer III feedforward projection neurons in schizophrenia. Altered hemispheric asymmetry of the PT has been reported in patients, along with altered white matter density in the corpus callosum, and there is anomalous activation of the PT during auditory hallucinations. We measured layer III cell density and pyramidal neuron size in PT of both hemispheres of post-mortem brains from patients with schizophrenia (n=16) and control subjects (n=16). We found reduced cell density and the loss of a correlation between magnopyramidal neuron density and axon number in the isthmus of the corpus callosum in schizophrenia. The normal asymmetry indicated that magnopyramidal neurons tend towards being larger and denser in the left PT but this asymmetry is significantly reduced in schizophrenia. The findings offer cytoarchitectural insight into the relationship between PT cortex and callosal white matter abnormalities in schizophrenia.